BONEKA TAWARAJA (CERITA WAYANG BERIRAMA JARI): MEDIA PEMBELAJARAN BAHASA INDONESIA DALAM PENINGKATAN PENDIDIKAN KARAKTER - Fetiyani Yuniana Ismawarsari; Risa Hafida Indradini; Puji Nur Hidayat (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The research objectives are (1) to find out how Tawaraja dolls are used forstorytelling and (2) to reveal the effectiveness of Tawaraja dolls used for puppetstorytelling and (3) to improve character education. The research was conducted inthe Bahasa Indonesia class in Bantul Timur Elementary School and the subjects werethe grade VB students. The method is research and development. This model isadopted from Borg and Gall’s theory. The steps are information collecting, planning,developing a preliminary form of product, preliminary field testing, revising the mainproduct, main field testing, conducting operational product revision, operational fieldtesting, revising the final product revision, and conducting dissemination andimplementation (Ghufron, 2005: 8). The result is the product of Tawaraja dolls aslearning media which are effective in developing the students’ character.